Normal enough? Krafft-Ebing, Freud, and homosexuality. (April 2021) - Lang, Birgit
This article analyses the slippery notions of the normal and normality in select works of Richard von Krafft-Ebing (1840–1902) and Sigmund Freud (1856–1939) and argues that homosexuality became a 'boundary object' between the normal and the abnormal in their works. Constructing homosexuality as 'normal enough' provided these two key thinkers of the fin de siècle with an opportunity to challenge societal and medical norms: Krafft-Ebing did this through mapping perversions; Freud, by challenging perceived norms about sexual development more broadly. The article submits that the scientific logic presented in Krafft-Ebing's seminal case study compilation Psychopathia Sexualis and Freud's early theoretical writings and cases, including Three Essays on the Theory of Sexuality (1905), was itself haunted by notions of norms and the normal that were not always easy to resolve, and sometimes involved a certain amount of inspired conjecture on the part of both thinkers in order to develop and validate their differing tripartite models of normality. Krafft-Ebing imagined homosexuality as a variation of the normal by generalizing a gay male experience. He also recorded the obstreperous cases of homosexual women based largely inside the clinic but by and large ignored this evidence. Freud inextricably bound homosexuality to normality (and vice versa) by redefining homosexuals as a group to include individuals with unconscious same-sex desire. Doing so allowed him to conceptualize the fear of homosexuality as crucial in the formation of neurosis and psychosis, and at the same time put him at odds with relevant early identity politics.